Implementasi Metode Problem Solving dalam Meningkatkan Pembelajaran Pendidikan Agama Kristen di Sekolah - Nova Ritonga; Juliandes Leonardo Trisno Mone; Mathan Yunip; Yunardi Kristian Zega (Jurnal Shanan, 2021)
Today's learning has used a student-centered learning model. In this learning, the teacher uses various learning methods which are certainly more interesting and involve students directly. This learning system is in accordance with the education standards and curriculum in 2013. Although the 2013 curriculum has implemented student-centered learning, until now there are still teachers including Christian religious education teachers who still use conventional methods (lectures) which cause the learning process is less interesting and tedious. Therefore, a breakthrough is needed that can improve Christian religious education learning in schools. Thus, the purpose of this study is to describe the implementation of problem solving methods in improving the learning process of Christian religious education in schools. The method used in this research is literature study with literature review using books, journals, dictionaries, and other sources to describe the implementation of problem solving methods in Christian religious education learning. The result of this research is that the implementation of problem solving methods can improve Christian religious education learning in schools because students are actively involved in the learning process.